(2x + 4) - (-x + 5)
= (2x + 4) -1(-x + 5)
= 2x + 4 + x - 5
= 2x + x + 4 - 5
= 3x - 1.
Answer:
2m-7
Step-by-step explanation:
Answer:
very easy just multiply 72 by 6 and the congroup the variable and the anser from mulpyiplication
Step-by-step explanation:
Answer:
144
Step-by-step explanation:
If you multiply 4 by 12, then add 100, you get 144 which is the area.
Answer:
"subtracting b, then dividing by m"
Step-by-step explanation:
To solve for a particular variable, look a the operations that are being performed on that variable. Then "undo" those operations in reverse order.
Here, the operations done to x are ...
• multiply by m
• add b to the product
Using the above recipe, first we "undo" the additon of b. We accomplish that by subtracting b from both sides of the equation. This gives ...
y - b = mx + b - b
y - b = mx . . . . . . . . . simplify
Next, we "undo" the multiplicatin by m. We accomplish that by dividing both sides of the equation by m.
(y -b)/m = mx/m
(y -b)/m = x . . . . . . . . simplify
This is your solution for x:
x = (y - b)/m
We found it by subtracting b, then dividing by m on both sides of the equation.